Dari Informasi ke Interaksi : Reposisi Peran Manajemen Humas Diera Digital Melalui Media Sosial: Penelitian - Arifia Retna Yunita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to anayze how public relations utilizes socia media as astrategy in increasing public interest in an organizationor activity. The appoach used is a quaitative method of case study desaign, in agencies that actively use socia media in their public relation activities. The result showed that the plandnned and directed use of socia media was able to increase public interest, which started out just providing information and turned into community interaction on socia media, expanding the reach of informationand increasing public participation and involvement. Key factors in this strategy include content consistency, two way interaction and utilization of platforms that are appropriate to the characteristics of the audience. The findings confirm the importance of transforming the role of public reation in the Digital age to form a more responsive and participatory relationship with the public.